The Effectiveness of Local Culture-Based Digital Teaching Materials in Enhancing High School Students’ Motivation in Physics Learning: A Literature Review - Cici Madiyawati; Sri Aliyah; Mirna Wahdaniyati; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Teacher Education, 2025)
The low level of motivation in learning physics among high school students is one of the main challenges in the learning process, often caused by the lack of connection between the material and students’ real-life contexts. One alternative solution is the implementation of digital teaching materials based on local culture, which can integrate physics concepts with students’ direct experiences. This study aims to examine the effectiveness of such teaching materials in improving high school students’ motivation to learn physics through the Systematic Literature Review (SLR) method. The study was conducted by analyzing various relevant scientific sources from several databases, with a publication range from 2016 to 2025. The initial search process yielded 120 articles, which were then selected through stages of identification, screening, and eligibility assessment, resulting in 10 articles that met the inclusion criteria for in-depth analysis. The analysis was carried out through data extraction, classification, and synthesis of research findings. The results show that local culture-based digital teaching materials, such as e-modules, modules, and interactive multimedia, have significant potential in improving students’ learning motivation. This improvement is reflected in increased learning interest, active student participation, conceptual understanding, and critical thinking skills. In addition, the integration of local culture makes learning more contextual, engaging, and meaningful by connecting physics concepts to students’ daily lives.